Quantification of Retinal Nonperfusion Associated With Posterior Segment Neovascularization in Diabetic Retinopathy Using Ultra-Widefield Fluorescein Angiography - Baxter, Sally L. (Ophthalmic Surg Lasers Imaging Retina, 2019)
BACKGROUND AND OBJECTIVE: To quantify the size and location of nonperfusion associated with posterior segment neovascularization (NV) in proliferative diabetic retinopathy (PDR) using ultra-wide- field fluorescein angiography. PATIENTS AND METHODS: Cross-sectional study of 18 eyes with PDR. The total image area, areas of nonperfusion, buds of posterior segment neovascularization (either neovascularization of the disc or elsewhere), and the distances from each bud to the nearest area of nonperfusion and to the disc were measured. RESULTS: Nonperfused areas with associated neo- vascularization were significantly larger than areas without neovascularization (32.0% ± 5.24% of the retinal image vs. 3.3% ± 0.92%; P < .001) and were more likely to be posteriorly located. Nonperfusion encompassing greater than 23% of the total angiographic image had more associated neovascular buds (9.64 ± 2.16 vs. 0.86 ± 0.29; P < .0001), which were closer to the disc (7.53 mm ± 0.27 mm vs. 9.24 mm ± 0.64 mm; P = .014). CONCLUSION: A threshold size of nonperfusion greater than 23% of the retinal image is associated with posterior segment neovascularization and may serve as an indicator of risk for the development of PDR.